2019
DOI: 10.4025/actascianimsci.v42i1.45371
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding inorganic and organic selenium sources on the hematological blood parameters, reproduction and health of dairy cows in the transition period

Abstract: The purpose of this study was to investigate the effects of four types of diets containing different forms of selenium on the hematological blood parameters, reproduction and health of dairy cattle during the transition period. Twenty-four close-up dry cows with a mean of 259 ± 1days of pregnancy and expected 21 ± 1days prior to parturition were selected. The cows were fed four diets: 1) basal diet without selenium supplementation (C); 2) basal diet plus 0.5ppm selenium in the form of sodium selenite (Se-S) 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
9
0
6
Order By: Relevance
“…In this context, antioxidant supplementation in the poultry diet is an interesting and affordable strategy to protect the meat from oxidation. Among the antioxidant supplements used, seleni-um (Se) is a micronutrient required mostly by animals and humans, that has attracted attention in recent years because of its dual role as a cofactor of the antioxidant enzyme GPx (Pascual and Aranda, 2013) and its important activity of strengthening the immune system as a component of selenoproteins and enzymes, its influence on the thyroid gland and anti-carcinogenic capacity (Hariharan and Dharmaraj, 2020).In previous works, it was shown that the expression of certain GPx enzymes could be strongly linked to selenium availability (Blas et al, 2013) in the diet, so Se supplementation could promote its activity in tissues, as previously reported in several species (Khalili et al, 2020;Wang and Xu, 2008). Besides, it was demonstrated that skeletal muscle is one of the major sites for selenium storage (Pascual and Aranda, 2013).…”
Section: Animals and Dietsmentioning
confidence: 66%
See 1 more Smart Citation
“…In this context, antioxidant supplementation in the poultry diet is an interesting and affordable strategy to protect the meat from oxidation. Among the antioxidant supplements used, seleni-um (Se) is a micronutrient required mostly by animals and humans, that has attracted attention in recent years because of its dual role as a cofactor of the antioxidant enzyme GPx (Pascual and Aranda, 2013) and its important activity of strengthening the immune system as a component of selenoproteins and enzymes, its influence on the thyroid gland and anti-carcinogenic capacity (Hariharan and Dharmaraj, 2020).In previous works, it was shown that the expression of certain GPx enzymes could be strongly linked to selenium availability (Blas et al, 2013) in the diet, so Se supplementation could promote its activity in tissues, as previously reported in several species (Khalili et al, 2020;Wang and Xu, 2008). Besides, it was demonstrated that skeletal muscle is one of the major sites for selenium storage (Pascual and Aranda, 2013).…”
Section: Animals and Dietsmentioning
confidence: 66%
“…Whereas when selenium is supplemented, selenomethionine, selenium-rich yeast, and sodium selenite are the organic and inorganic forms used, and they vary in the absorption, efficiency, and metabolism mechanisms (Hariharan and Dharmaraj, 2020). Several studies in different species have indicated that selenomethionine could be more effective than inorganic sources, selenite or selenate (Ali et al, 2020;Juniper et al, 2008;Vignola et al, 2009;Yanyan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…No se observaron deficiencias de selenio en sangre, los tres grupos mantuvieron niveles adecuados durante todo el experimento. Se ha observado que la suplementación con el mineral incrementa los niveles de selenio en sangre en vacas lecheras (Khalili, et al, 2020), cerdos (Cao et al, 2014, en pollos (Doaa et al, 2019), borregos (Ademi et al, 2017 y cabras (Ziaei, 2015), con efectos benéficos en la salud y la producción animal; sin embargo, un exceso del mineral en la dieta puede llegar a tener efectos negativos en la productividad con la consecuente intoxicación de los animales y la muerte (Żarczyñska et al, 2013). Se observó que hubo variaciones en las concentraciones de selenio a lo largo del experimento para todos los grupos.…”
Section: Discussionunclassified
“…There is evidence indicating that selenium deficiency increases the frequency of abortions (Hedstrom et al, 1986). The use of selenium drugs reliably prevents these pathological processes (Giadinis et al, 2016;Khalili et al, 2020).…”
Section: Mineralsmentioning
confidence: 99%